PEMAKAIAN MEDIA SOSIAL DAN SELF CONCEPT PADA REMAJA - Pamela Felita; Christine Siahaja; Vania Wijaya; Gracia Melisa; Marcella Chandra; Rayini Dahesihsari (MANASA, 2016)
Teenager is among the biggest number of society consuming social media in Indonesia. The initial reason they become so active in social media is to get attention, to seek for opinion, and also to present their image. However, in the long term they become addicted of social media consumption. It is difficult for them to stay away from activities related to social media. Although social media in general has a positive side to be consumed, the overused of social media has a negative consequence. A bulk of studies shown that the overused of social media by teenager give consequences on the increase of self concept incongruence because there is a large distance between the real self and the ideal self. The self presenting in social media is the ideal self which has such a large distance from the real self. Teenagers are enjoying the ideal self of them presenting in social media so that they prefer to stay in social media rather than their daily activities of real self. This manuscript aims to describe the data collection which being used to propose campaign of decreasing consumption of social media for teenager, particularly which damage their self concept. 150 teenagers and young adult participated, the range of age was 15-25 years old. All of them were actively using of social media. Survey was used for data collection. The result showed that most of the participants want to look good at their social media profile by presenting their ideal self, even though it is not the image that they have in the real self. Based on the data, the campaign of decreasing consumption of social media is design. The campaign is focused on how to develop the positive self concept without overused consumption of social media. By decreasing consumption of social media, teenagers would be more productive and develop their positive self concept in their real life.